The reputation of the modern royal houses of the Spanish Bourbon and Windsor - S. K. Makayeva (Ибероамериканские тетради, 2019)
The aim of the present invesiigaiion is to identify particular characteristics of the reputation of members of the Royal families of Spain and the UK and comparison them. Analysis of the materials showed that the reputation of the two Royal families, as well as the families themselves, is very different. The Royal family of Britain has an impeccable reputation, and the reputation of the representatives of the Spanish monarchy has been repeatedly tested over the past ten years. However, since the accession of Philip VI to the throne, the reputation of the Bourbons began to recover gradually. What unites the two Royal families is the desire to preserve the crown and the approval of their subjects. Both dynasties try to maintain the image of the monarch as a source of enduring permanence in the changing Spain and the UK, as a symbol of unity and cohesion of the nation. The main task of each Royal house today is to preserve the prestige of the Institute. For subjects to consider them useful and necessary, nothing should undermine their image and reputation. Monarchies should keep up with the times.